TRANSFORMASI PONDOK PESANTREN DALAM ERA MODERNISASI ZAMAN (STUDI PONDOK PESANTREN NURUL JADID AL SYARIFAL ISLAMY DESA RAMBUTAN MASAM KECAMATAN MUARA TEMBESI KABUPAT BATANG HARI PROVINSI JAMBI) - Indah Sari, Yunica; Tamirano , Randi (UIN Sulthan Thaha Saifuddin Jambi, 2025)
Abstract This research is motivated by the existence of the Islamic boarding school education system in facing the era of modernization. The main focus of this research is the Nurul Jadid Al Syarif Al Islamy Islamic Boarding School located in Rambutan Masam Village, Muara Tembesi District, Batang Hari Regency, Jambi Province. The purpose of this study is: The Islamic Boarding School Education System in the Era of Modernization (Study of the Nurul Jadid Al Syarif Al Islamy Islamic Boarding School in Rambutan Masam Village, Muara Tembesi District, Batang Hari Regency, Jambi Province). The type of research used is a qualitative-descriptive approach, by describing the form of the Existence of the Islamic Boarding School Education System in the era of modernization. This study uses a purposive sampling technique. Data collection in the form of observation, interviews and documentation with data analysis techniques, namely data reduction, data presentation and drawing conclusions. Based on the results of the study, it shows that the Nurul Jadid Al Syarif Al Islamy Islamic Boarding School still maintains the principles of traditional education based on religion, but also begins to integrate a curriculum that is relevant to the demands of the modern world, such as technology and general science lessons. Thus, this Islamic boarding school is able to adapt and maintain its existence amidst rapid social and technological changes, although challenges in terms of financing, human resources, and facilities still need to be overcome. This study is expected to contribute to the development of an Islamic boarding school education system that is relevant to the needs of the times without ignoring the religious values ​​contained therein.